Considering Systemic Barriers to Treating Tobacco Use in Clinical Settings in the United States. Issue 11 (15th June 2018) - Rojewski, Alana M; Bailey, Steffani R; Bernstein, Steven L; Cooperman, Nina A; Gritz, Ellen R; Karam-Hage, Maher A; Piper, Megan E; Rigotti, Nancy A; Warren, Graham W
Abstract: The Comorbidity Workgroup of the Tobacco Treatment Research Network, within the Society for Research on Nicotine and Tobacco, previously highlighted the need to provide tobacco treatment to patients diagnosed with comorbid physical and mental health conditions. Yet, systemic barriers in the United States health care system prevent many patients who present for medical treatment from getting the evidence-based tobacco treatment that they need. The identified barriers include insufficient training in the epidemiologic impact of tobacco use, related disorders, and pharmacological and behavioral treatment approaches; misunderstanding among clinicians about the effectiveness of tobacco treatment; lack of therapeutic support from clinical staff; insufficient use of health information technology to improve tobacco use identification and treatment; and limited time and reimbursement for clinicians to provide treatment. We highlight three vignettes demonstrating the complexities of practical barriers at the health care system level. We consider each of the barriers in turn and discuss evidence-based strategies that could be implemented in the clinical care of patients with comorbid conditions. In addition, in the absence of compelling data to guide implementation approaches, we offer suggestions for potential strategies and avenues for future research. Implications: Three vignettes highlighted in this article illustrate some systemic barriers to providing tobacco treatment for patients being treated for comorbid conditions. We explore the barriers to tobacco treatment and offer suggestions for changes in training, health care systems, clinical workflow, and payment systems that could enhance the reach and the quality of tobacco treatment within the US health care system.